Robust Controller for a Vision Feedback Based Telepointer - Shah Newaz Mohammad Abdul Kader; Mohd. Marzuki Mustafa; Aini Hussain (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Telepointer is a very useful tool for teleconsultation and teleproctoring, whereby a telepointer via teleconferencing is a perfect example of computer-supported cooperative work (CSCW) and digital telepresence. To this end, many telepointers are introduced for digital telepresence. However, there are still concerns regarding the speed of response and robustness of the system. It is rather difficult to model the actual system in order to design the controller. This paper described the development of a telepointer and its controller for a real time communication using vision feedback. The main focus of this study was to control the Laser Pointer (LP) with a discrete time PID (proportional–integral–derivative) controller which was tuned using Ziegler-Nichols (ZN) method. The results indicated that the tuned controller bring about fast response with no overshoot and steady state errors at the output response. The controller was shown to be robust against changes in sampling time and external disturbance.